Effectiveness of Gold Extraction with Thiourea Solution from Gold Rocks in Mount Tumpang Pitu Pasanggaran Banyuwangi - Andarini, Novita; Ramadhani, Ferlia Suci; Haryati, Tanti; Suwardiyanto (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2024)
This research aims to determine the effect of adding an oxidizing solution in the gold extraction process using thiourea solution. The oxidizing agent used in thiourea leaching solution is FeCl3. Variations of additional volume of oxidizing solution are 0 mL, 10 mL, 20 mL, 30 mL, and 40 mL. Based on the results obtained, the addition of 30 mL oxidant FeCl3 can get optimal results. The thiourea leaching solution can extract gold as much as 46.7%.